2022
DOI: 10.3349/ymj.2022.63.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Suppression and Systemic Immune Activation of Macrophages through the Sting Pathway in Metastatic Skin Tumor

Abstract: Purpose Agonists of the stimulator of interferon genes (STING) play a key role in activating the STING pathway by promoting the production of cytokines. In this study, we investigated the antitumor effects and activation of the systemic immune response of treatment with DMXAA (5,6-dimethylxanthenone-4-acetic acid), a STING agonist, in EML4-ALK lung cancer and CT26 colon cancer. Materials and Methods The abscopal effects of DMXAA in the treatment of metastatic skin nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…T cells from skin-derived inflammatory diseases exhibit differential gene expression patterns, including genes known to be involved in immune activation in cancer 44 . Specifically, in tumors, IFN-related genes are recognized to activate T cells and play a crucial role in tumor infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…T cells from skin-derived inflammatory diseases exhibit differential gene expression patterns, including genes known to be involved in immune activation in cancer 44 . Specifically, in tumors, IFN-related genes are recognized to activate T cells and play a crucial role in tumor infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…5,6-Dimethylxanthenone-4-acetic acid (DMXAA), a flavonoid with putative anti-tumor activity, was originally developed as an anti-angiogenic agent and was later found to interact directly with STING [ 59 ]. Although phase III clinical trials did not demonstrate any improvement in the prognosis of NSCLC patients treated with DMXAA in combination with standard chemotherapy [ 60 ], researchers have revealed that the expression levels of TNF-α, IFN-β, and STING were significantly up-regulated in EML4-ALK NSCLC tumors after DMXAA treatment, which resulted in the inhibition of tumor growth and the induction of strong anti-tumor immunity in EML4-ALK NSCLC mouse models [ 61 ]. EML4-ALK is a unique molecular subgroup of lung cancer that is resistant to checkpoint inhibitors [ 62 ].…”
Section: The Regulation Of Sting Activation By Various Factors In Nsclcmentioning
confidence: 99%
“…Conversely, upon stimulation with lipopolysaccharide and interferon (IFN)-γ, RLN does not affect Arg-1 expression but promotes the upregulation of iNOS expression. This suggests a mechanism distinct from the classical mechanism of macrophage polarization [ 99 , 105 ]. RLN-RXFP1 signaling stimulates the secretion of IL-1β and TNF-α in PBMCs [ 106 ].…”
Section: Treatment Strategy Through Ecm Degradation and Rln Immunomod...mentioning
confidence: 99%